Variability of ENSO teleconnections indices, and its impacts on Moroccan Agriculture - Peethani, Sujatha; Pathakoti, Mahesh; V, Mahalakshmi D.; Kheir, Ahmed MS.; Singh, Apoorva; Govind, Ajit (Elsevier, 2024)
In Morocco, drought periods have become more frequent and severe due to climate change, which has had a substantial effect on freshwater supply and agricultural output. The El Niño-Southern Oscillation (ENSO) and the influence of climatic variability were the main subjects of the current study, which made use of daily precipitation, maximum and minimum temperature data collected at 50 locations around the nation from 1990 to 2022. The study analysed Palmer Drought Severity Index (PDSI) over Morocco to evaluate the impact of climate indices such as the Oceanic Niño Index (ONI) and the North Atlantic Oscillation (NAO) on drought severity. It also investigated the changes in precipitation, temperature, and extreme event-related indices. Rainfall is used as a proxy for El Nino and La Nina, supported by a negative and significant correlation between Oceanic Nino Index (ONI) and rainfall. Attempted to understand the impact of the NAO on Morocco's agricultural production, particularly during the winter months. During negative NAO phases, winter temperatures can lead to reduced wheat yields by 35–45% during the El Niño years and decreased by 4–7% during the La Niña years compared to the actual yield. Relying on the NAO plays a crucial role in modulating the precipitation patterns, which implies that crop requires adequate soil moisture with no extreme temperature during the growing season in order to produce higher yield. ENSO events can indeed lead to these extreme conditions in selected locations, potentially impacting crop yields.